2016
DOI: 10.1177/0265532216643630
|View full text |Cite
|
Sign up to set email alerts
|

China Accreditation Test for Translators and Interpreters (CATTI): Test review based on the language pairing of English and Chinese

Abstract: Test purpose: The CATTI aims to measure competence in translation and interpreting (including simultaneous and consecutive interpreting 2 ) between Chinese and seven foreign languages: English, Japanese, French, Arabic, Russian, German, or Spanish. The test is intended to cover a wide range of domains including business, government, academia, and media, though it is not designed to assess literary translation.Length and administration: The CATTI test battery is divided into four levels of Senior, I, II, and II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Findings of the present study indicated that the specialized translation exams currently used at COLT have many shortcomings and they do not meet the criteria of a good test in terms of reliability, validity, discrimination power, authenticity, variability, and other test features mentioned by prior researchers such as [4]; [12]; [19]; [7]; [13]; [14]; [6]; [16]; [15]; [2]; [5]; [1]; [17]; [18]; [20]; [21]; [3].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of the present study indicated that the specialized translation exams currently used at COLT have many shortcomings and they do not meet the criteria of a good test in terms of reliability, validity, discrimination power, authenticity, variability, and other test features mentioned by prior researchers such as [4]; [12]; [19]; [7]; [13]; [14]; [6]; [16]; [15]; [2]; [5]; [1]; [17]; [18]; [20]; [21]; [3].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…A second line of research focused on criteria that have to be taken into consideration in translation assessment. Those criteria included: (i) employing a psychometrically based approach to the development of translation tests [2]; (ii) the source texts should be authentic, self-contained, comprehensible, and not previously covered [5]; (iii) authenticity of the translation task (Wu and Stansfield, 2001) [6]; (iv) specifying the types of knowledge required in text comprehension and translation which include linguistic, encyclopaedic, interactive, metacommunicative, and global textual knowledge [1]; (v) reliability, validity, practicality, and fairness of the translation test [4]; [12], [13]; [14]; [15]; [16]; [17]; [7]; [18], construct, criterion-related and concurrent validity [19]; [12]; [20]; (vi) objectivity and scorability [20]; (vii) accuracy of translation tests as competence evaluation rather than source/target text comparisons [21]; and (viii) allowing the students to bring two bilingual paper dictionaries, but no electronic devices [3].…”
Section: Introductionmentioning
confidence: 99%
“…All of the participants have acquired level two Certificate of China Accreditation Test for Translators and Interpreters (CATTI), three of them acquired level one Certificate. CATTI is the most authoritative interpreting proficiency qualification accreditation test, level two certificate holders are assumed with the capability of interpreting political speeches (Chen, 2009;Zhao & Gu, 2016). No one among them had been to East Africa or interpreted speeches from an East African speaker.…”
Section: Participantsmentioning
confidence: 99%
“…However, one area of oral communication—spoken-language interpreting—seems to have drawn far less attention from language testers than it rightfully deserves, given that interpreting, in and of itself, is language-mediated communication. A review of the two prominent language testing journals, Language Testing (1984–2020) and Language Assessment Quarterly (2004–2020), produced only four publications that center on spoken-language interpreting (i.e., Han, 2016, 2019; Stansfield & Hewitt, 2005; Zhao & Gu, 2016) or what is known as interpreting testing and assessment (hereafter ITA). The lack of testers’ attention to (oral) interpreting stands in sharp contrast to its counterpart of written translation, which has long been practiced as a pedagogical exercise in L2 teaching (e.g., grammar translation method), studied by early language testing researchers (e.g., Lado, 1961), and which has recently reinvigorated interest among L2 educators and applied linguists (e.g., Cook, 2010).…”
mentioning
confidence: 99%